Certain Concepts of Q-Hesitant Fuzzy Ideals. (22nd July 2022) - Alleheb, Lubna Abdul Aziz; Alsager, Kholood Mohammad
Abstract : The hesitant fuzzy set model has attracted the interest of scholars in various fields. The striking framework of hesitant fuzzy sets is keen to provide a larger domain of preference for fuzzy information modeling of deployment membership. Starting from the hybrid properties of hesitant fuzzy ideals (HFI), this paper constructs a new generalized hybrid structure Q -HFI. The concept of Q -hesitant fuzzy exchange ideal in B C K -algebra is considered. Lastly, Q -hesitant fuzzy exchange ideal features are described.